Pembelajaran Bahasa Arab untuk Anak Usia Dini: Studi Kasus RA Al Akhyar Jakarta Selatan - Azzahro, Fatimah; Salama, Hartini (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2025)
This research is motivated by the limited number of studies on Arabic language learning for early childhood at the Raudhatul Athfal (RA) level. The purpose of this study is to explore Arabic language teaching methods in RA, with a specific focus on RA Al Akhyar in South Jakarta. The research employs a qualitative approach using a descriptive method. The research subjects were selected through purposive sampling. The chosen sample is Raudhatul Athfal Al Akhyar, located in East Cilandak, South Jakarta. Data were collected using observation and interview instruments. To understand teaching practices, data analysis was carried out using thematic techniques, involving data reduction and categorization based on the applied teaching methods, which were then interpreted. The results indicate that Arabic language learning at RA Al Akhyar uses a contextual and joyful approach, as reflected in the materials, methods, and media utilized. The teaching emphasizes multisensory and experiential learning approaches. For evaluation, authentic assessment is applied. The findings also reveal challenges, particularly the slow response of some students. It is concluded that students show better understanding when learning is delivered in an interactive and enjoyable manner. Although the current practice aligns with early childhood education principles, strengthening the curriculum and providing teacher training are still needed to enhance the effectiveness of Arabic language instruction at RA Al Akhyar. This study contributes to filling the gap in discussions on Arabic language learning for early childhood, particularly within the RA context